1990
DOI: 10.1177/036354659001800202
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic evaluation of shoulder rotational strength between the plane of scapula and the frontal plane

Abstract: The purpose of this study was to determine whether shoulder rotational strength was greater in the plane of the scapula or the frontal plane. Isokinetic shoulder rotational strength was evaluated in 20 subjects. Using the Merac (Universal Gym Equipment, Inc., Cedar Rapids, IA), test data was gathered in the right shoulders, in 45 degrees abduction, at a speed of 60 deg/sec, in the plane of the scapula and the frontal plane. Each subject returned within 1 week for retests to establish reliability. The average c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
5

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 14 publications
4
74
0
5
Order By: Relevance
“…The highest QAREL rating was 6/11, with an average of 4.2 ± 1 (range 2-6). Numbers and methodological quality of studies dealing with supine and standing positions were poor: 6 studies 11,20,26,33,34,40 for 3 positions, with QAREL scores from 2 to 4. Individual QAREL scores for each included study are reported in Table 2.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
“…The highest QAREL rating was 6/11, with an average of 4.2 ± 1 (range 2-6). Numbers and methodological quality of studies dealing with supine and standing positions were poor: 6 studies 11,20,26,33,34,40 for 3 positions, with QAREL scores from 2 to 4. Individual QAREL scores for each included study are reported in Table 2.…”
Section: Methodological Quality Of the Studiesmentioning
confidence: 99%
“…7,10,40,43 Several studies documented the electromyographic (EMG) activity of the glenohumeral musculature during specific shoulder exercises. 3,5,6,13,22,25,26,28,38,47 Townsend et al 38 determined that the best exercise for the infraspinatus muscle was to perform prone shoulder horizontal abduction with external rotation (ER), producing 88% of maximal voluntary isometric contraction (MVIC), while the most effective exercise for the teres minor muscle was sidelying ER, producing 80% MVIC. In a different study comparing ER in the scapular and frontal planes during isokinetic testing, Greenfield et al 13 suggested that the highest amount of muscle activity for the external rotators occur when the shoulder is in the scapular plane.…”
mentioning
confidence: 99%
“…The shoulder joint IR and ER movements were measured as the arms of the athletes were at 45° abduction in the scapular plane and the shoulders were at 90° flexion. This position was selected because the stress on the rotator cuff was minimal in this position compared with the position where the arms were at 90° abduction in the frontal plane (12,22). On the contrary, previous studies reported that this position was the most reliable position for assessing the shoulder IR and ER strength (14).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, objective assessment of muscle strength in all athletes is crucial to the sportive success of athletes and prevention of injuries. Despite several studies in the literature exploring the upper extremity isokinetic strength profile in various sports fields such as swimming, handball, volleyball, tennis, water polo, cricket, judo, and basketball (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), no study has examined the upper extremity isokinetic muscle strength characteristic in weightlifters.…”
Section: Introductionmentioning
confidence: 99%